Microprocessor Structure with Ratio Control Action Based on Annotated Paraconsistent Logic (Research, Society and Development, 2022)
This article presents the construction of a micro-controlled structure with algorithms based on Paraconsistent Annotated Logic composing a network of signal analyzes with the purpose of acting as a reason station in loop control for liquid mixture. The Paraconsistent Ratio Station was implemented on an open-source Arduino electronic board that has an ATmega328P microcontroller. The ratio control is configured with two controllers acting with PID-Proportional+Integral+Derivative actions and this type control action is widely used in industrial mixing processes. One of the main problems in this type of control is that there are imbalances between the communication between two controllers when there are changes that do not adjust the set point and the controlled variable, causing percentage differences between the quantities or that can make the quality of the final product unfeasible. Therefore, the objective of the research was to contribute to mitigate the harmful effects on production when changes are made to the controllers set point. In the proposed algorithmic structure it is used algorithms based on Paraconsistent Logic (PL) that is a non-classical logic capable of supporting contradictory signals that makes it advantageous to its application in relation to classical binary logic. The hardware of Paraconsistent Ratio Station was simulated in the laboratory and in an experimental control scheme, presenting superior results to ratio systems that use conventional logic.